PENINGKATAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS IV-A SDN MARGOREJO 1/403 SURABAYA MELALUI PERMAINAN JURAGAN KEBUN CERDAS DALAM PEMBELAJARAN BANGUN DATAR - Putri Wihatma Andianti; Rarasaning Satianingsih; Novi Indria Wardani; Okania Sri Purwaningrum; Hanifah Khoirunnisa; Lucky Juniar Rachman; Jauharul Ifadhi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to enhance the critical thinking skills of fourth-grade students at SDN Margorejo 1/403 Surabaya through the implementation of the group educational game